How Brand Score/Equity can Affect Branding Strategy Development - Srivastava, R. K.; Thakar, K. (Indian Journal of Marketing, 2004)
Brand is a source of relationships with customers, promises to customers and customer loyalty, Great brands present emotional benefits and not just rational/functional benefits. Branding is a process of creating an association between a symbol/object/emotion/perception and a product/company with a goal of driving loyalty and creating differentiation. Branding is raising new questions for brand managers like what benefits and expectations customers look across a brand, how consistent in the brand image, etc. Brand Score is a type of brand measurement system. It is also referred as 'Brand Metrics'. Brand Score is a systematic tool, which can be used to gauge and evaluate Brand Performance, which in turn would help to adjust the Brand Strategy.